The palms of South America: diversity, distribution and evolutionary history - Pintaud, Jean-Christophe (2008)
This article presents an inventory of South American palms including 457 species and 50 genera. The distribution of palms within seven phytogeographical entities is analyzed. Factors which influence the evolution of palms in South America are discussed.